2018
DOI: 10.3389/fpsyg.2018.01868
|View full text |Cite
|
Sign up to set email alerts
|

Insights From fMRI Studies Into Ingroup Bias

Abstract: Intergroup biases can manifest themselves between a wide variety of different groups such as people from different races, nations, ethnicities, political or religious beliefs, opposing sport teams or even arbitrary groups. In this review we provide a neuroscientific overview of functional Magnetic Resonance Imaging (fMRI) studies that have revealed how group dynamics impact on various cognitive and emotional systems at different levels of information processing. We first describe how people can perceive the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 94 publications
1
46
0
Order By: Relevance
“…On a biological level, the consolidation of new identity to action links are underpinned by the neuroscience of intergroup relations (Molenberghs & Louis, 2018) and collective action (Zak & Barraza, 2013). For the purposes of this article, such work is still in its infancy: It does not explore the multivariate complexity of choices among collective actors' tactics for example.…”
Section: Efforts Can Rekindlementioning
confidence: 99%
“…On a biological level, the consolidation of new identity to action links are underpinned by the neuroscience of intergroup relations (Molenberghs & Louis, 2018) and collective action (Zak & Barraza, 2013). For the purposes of this article, such work is still in its infancy: It does not explore the multivariate complexity of choices among collective actors' tactics for example.…”
Section: Efforts Can Rekindlementioning
confidence: 99%
“…One piece of evidence for this is the well-known feature of human behavior: ingroup bias. The feeling of group belongingness is known to bias empathy and helping attitudes among diverse social groups (Molenberghs, 2013;Cikara and Van Bavel, 2014;Hackel et al, 2017;Molenberghs and Louis, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Extensions to neuroscience research have been made increasingly apparent (for a recent 117 review see Molenberghs and Louis, 2018;Hackel et al, 2017). A recent example comes from 118 Lin et al, (2018), who found that after participants rated emotional stimuli in the scanner, 119 they were more likely to change their evaluations to be more similar to the evaluations other 120 in-group members made compared to the out-group.…”
Section: Introduction 48mentioning
confidence: 99%